Multiple-Dose Pharmacokinetics and Tolerability of Gemifloxacin Administered Orally to Healthy Volunteers - Allen, Ann (American Society for Microbiology, 2001)
Gemifloxacin mesylate (SB-265805-S, LB-20304a) is a potent, novel fluoroquinolone agent with a broad spectrum of antibacterial activity. The pharmacokinetics and tolerability of oral gemifloxacin were characterized in two parallel group studies in healthy male volunteers after doses of 160, 320, 480, and 640 mg once daily for 7 days. Multiple serum or plasma and urine samples were collected on days 1 and 7 and were analyzed for gemifloxacin by high-performance liquid chromatography (HPLC)–fluorescence (study 1) or HPLC-mass spectrometry (study 2). Safety assessments included vital signs, 12-lead electrocardiogram (ECG) readings, hematology, clinical chemistry, urinalysis, and adverse experience monitoring. Gemifloxacin was rapidly absorbed, with a time to maximum concentration of approximately 1 h after dosing followed by a biexponential decline in concentration. Generally, maximum concentration and area under the concentration-time curve (AUC) increased linearly with dose after either single or repeat doses. Mean ± standard deviation values of AUC(0–τ) on day 7 were 4.92 ± 1.08, 9.06 ± 2.20, 12.2 ± 3.69, and 20.1 ± 3.67 μg·h/ml following 160-, 320-, 480-, and 640-mg doses, respectively. The terminal-phase half-life was approximately 7 to 8 h, independent of dose, and was similar following single and repeated administrations. There was minimal accumulation of gemifloxacin after multiple dosing. Approximately 20 to 30% of the administered dose was excreted unchanged in the urine. The renal clearance was 160 ml/min on average after single and multiple doses, which was slightly greater than the accepted glomerular filtration rate (approximately 120 ml/min). These data show that the pharmacokinetics of gemifloxacin are linear and independent of dose. Gemifloxacin was generally well tolerated, although one subject was withdrawn from the study after 6 days at 640 mg for mild, transient elevations of alanine aminotransferase and aspartate aminotransferase not associated with any clinical signs or symptoms. There were no other significant changes in clinical chemistry, hematology or urinalysis parameters, vital signs, or ECG readings. In conclusion, the results of these studies, combined with the antibacterial spectrum and potency, support the further investigation of once-daily administration of gemifloxacin for indications such as respiratory tract and urinary tract infections.